2017
DOI: 10.1007/s10456-017-9567-4
|View full text |Cite
|
Sign up to set email alerts
|

A new key player in VEGF-dependent angiogenesis in human hepatocellular carcinoma: dimethylarginine dimethylaminohydrolase 1

Abstract: BackgroundAnti-angiogenic therapies, targeting VEGF, are a promising treatment for hepatocellular carcinoma (HCC). To enhance this potential therapy, identification of novel targets in this pathway is of major interest. Nitric oxide (NO) plays a crucial role in VEGF-dependent angiogenesis. NO production depends on arginine as substrate and asymmetric dimethylarginine (ADMA) as inhibitor. Dimethylarginine dimethylaminohydrolase 1 (DDAH-1) catabolizes ADMA and therefore regulates NO and VEGF expression. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…Nonetheless, in addition to DDAH overexpression, DDAH1 was associated with IBD angiogenesis as VEGFA and TP53 were independent predictors of its expression in both quiescent and inflamed bowel. Those findings corroborate recent reports on DDAH1 being a new player in VEGF-dependent angiogenesis in human hepatocellular carcinoma [48] and glioma [49]. DDAH2, in turn, has been implicated in angiogenesis in lung adenocarcinoma [50].…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, in addition to DDAH overexpression, DDAH1 was associated with IBD angiogenesis as VEGFA and TP53 were independent predictors of its expression in both quiescent and inflamed bowel. Those findings corroborate recent reports on DDAH1 being a new player in VEGF-dependent angiogenesis in human hepatocellular carcinoma [48] and glioma [49]. DDAH2, in turn, has been implicated in angiogenesis in lung adenocarcinoma [50].…”
Section: Discussionsupporting
confidence: 92%
“…VEGF is a critical driver of sprouting angiogenesis that functions by regulating vascular formation, remodeling and permeability. Aberrant expression and activation of VEGF usually occurs in most solid tumor microenvironments, including breast cancer (20,21). The present study next clarified the effects of RRM2 on VEGF levels and found that RRM2 knockdown dampened the expression and release of VEGF in breast cancer cells.…”
Section: Discussionmentioning
confidence: 53%
“…; Buijs et al. ). Studies in transgenic mice over‐expressing DDAH1 showed lower plasma levels of ADMA, increased NO production, and NOS activity (Dayoub et al.…”
Section: Introductionmentioning
confidence: 98%
“…There are two isoforms encoded by two different genes DDAH1 and DDAH2 (Leiper et al 1999;Tran et al 2003;Vallance and Leiper 2004;Pope et al 2009b;Janssen et al 2013). DDAH1 is the main isoform for ADMA degradation in vivo (Pope et al 2009a;Buijs et al 2017). Studies in transgenic mice over-expressing DDAH1 showed lower plasma levels of ADMA, increased NO production, and NOS activity (Dayoub et al 2003;Jacobi et al 2005), as well as enhanced angiogenesis after ischemia or inflammation (Jacobi et al 2005).…”
Section: Introductionmentioning
confidence: 99%